2014
DOI: 10.4103/0970-2113.125913
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis with pleural effusion in an immunocompetent patient

Abstract: Visceral leishmaniasis (VL) is usually characterized by splenomegaly, pallor and fever. Pleural effusion is an uncommon feature of this disease, which is encountered in immunocompromised patients. Here, we report a case of VL with pleural effusion in an immunocompetent patient. Pulmonary symptoms in VL are usually related to bacterial lung infection, vagal nerve compression by splenomegaly, and hypoalbuminaemia with mild pulmonary edema. Our patient presented with cough and chest pain. The clinical features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Previous studies have shown that COPD is related to lysosome,45 Staphylococcus aureus infection,46 osteoclast differentiation,47 leishmaniasis,48 dilated cardiomyopathy,49 rap1 signaling pathway,50 and PPAR signaling pathway,51 which are concordant with our KEGG pathway results in patients with COPD. In addition, we found 1,115 up-regulated and 346 down-regulated GO terms in biological process, 127 up-regulated and 34 down-regulated GO terms in cellular component, and 115 up-regulated and 53 down-regulated GO terms in molecular function between COPD lung tissues and non-COPD lung tissues according to the GO analysis results.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that COPD is related to lysosome,45 Staphylococcus aureus infection,46 osteoclast differentiation,47 leishmaniasis,48 dilated cardiomyopathy,49 rap1 signaling pathway,50 and PPAR signaling pathway,51 which are concordant with our KEGG pathway results in patients with COPD. In addition, we found 1,115 up-regulated and 346 down-regulated GO terms in biological process, 127 up-regulated and 34 down-regulated GO terms in cellular component, and 115 up-regulated and 53 down-regulated GO terms in molecular function between COPD lung tissues and non-COPD lung tissues according to the GO analysis results.…”
Section: Discussionsupporting
confidence: 91%
“…VL is a disease characterized by systemic involvement and a broad spectrum of clinical manifestations. Pulmonary involvement in this parasitosis is even considered uncommon in immunocompetent patients [17]. However, the frequency of respiratory symptoms and tomographic changes found in the present study demonstrate that the involvement of the respiratory system in VL is more common than previously thought and deserves attention.…”
Section: Discussionmentioning
confidence: 42%
“…Chest X-ray revealed pneumonia in only two patients in the study, and both reported respiratory symptoms. Nodular tomographic pattern and increased pulmonary opacity found in our sample are considered suggestive of interstitial disease, but may also be due to bacterial infection [17,31]. Thus, the frequency of secondary bacterial pneumonia may be higher than that found on plain radiographs.…”
Section: Normal-n (%) Changed-n (%) P-valuementioning
confidence: 53%
See 1 more Smart Citation
“…In bone marrow and peripheral blood smear, Leishmania amastigotes were observed. Intravenous sodium stibogluconate started and pleural effusion resolved after one month (13).…”
Section: Discussionmentioning
confidence: 99%